Seedbeds for wheat and grasses - Schuler, Martin Roy (My University, 1906)
Introduction: Alfalfa would probably have been grown in Kansas as a staple crop long before it was generally recognized as such, if those who first introduced it into the state had more thoroughly understood the nature of leguminous plants. Many attempts were made to grow alfalfa which resulted in failures because the work of preparing the seedbed for the crop was done in the same manner that all farm work was done in the early history of Kansas. All that was thought necessary was to turn over the sod; plant the seed and expect a crop. If a few farmers tried to grow alfalfa and through lack of the proper conditions of the seedbed the crop was not a success, it was given up as a crop not adapted for that particular section of the state in which the attempt was first made to raise it. Thus it is with many agricultural crops, the reason why they do not prove profitable is because they do not receive proper attention. The preparation of seedbeds, although a subject which probably interested Adam, and has interested every peasant and farmer since his time, is today a subject in which every tiller of the soil is interested - in fact every producer of wealth is interested. Not only must it be necessary for the successful agriculturist and farmer of the twentieth century to thoroughly understand, at least the fundamental and rudimentary principles of tillage but it should be an interesting and pleasant study to thoroughly understand the moisture problems which he has to solve, as related to soil texture, to the conservation of soil moisture, and the relation of bacteria to soil fertility and plant growth. To a lack of interest on the part of some and indifference of others is due the fact that even today certain methods of farming are in practice simply because these methods were used by the preceeding generations. These methods may be and often are, entirely out of date. Some make attempts to learn why work ought to be done and how best to do it, but many do not. If the practical man takes no interest in the study of agriculture he can have little if any real pleasure in his work and financially he will be far behind the man who farms scientifically.
Citation: Schuler, Martin Roy. Seedbeds for wheat and grasses. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Horticultured; Seed Beds; Wheat; Grasses; Kansas; Theses